The impact of anthelmintic resistance on beef cattle productivity - Cantón, Candela (2017)
The goal of the current study was to evaluate, in a commercial beef-cattle farm, theimpact of anthelmintic resistance (AR) on the productivity of calves naturally infectedwith gastrointestinal nematodes resistant to ivermectin (IVM) and moxidectin(MXD).This trial included two herds grazing on different forage resources: Herd A ina maize-winter forage crop rotation (low re-infection) and Herd B in a two-year-oldAgropyrum pasture (high re-infection). In each herd, eighty male calves wererandomly allocated into four groups (n= 20): Control group (CG): without anthelmintictreatment; IVM group: treated with IVM (0.2 mg/kg); MXD group: treated with MXD(0.2 mg/kg); IVM+RBZ group: treated with IVM and ricobendazole (RBZ) (0.2 and3.75 mg/kg, respectively). All treatments were given by the subcutaneous route. Theclinical efficacy was determined by FECRT 20 days post-treatment. On days 0, 20,35, 67 and 90, individual weights were registered. The clinical efficacies were 42%(IVM), 67% (MXD) and 99% (IVM+RBZ). Cooperia spp. and Haemonchus spp.were the genera involved in AR. In Herd A the total weight gains (TWGs) in the 90day-period increased by 0% (IVM), 59% (MXD) and 90% (IVM+RBZ) compared withthe Control group. In Herd B the TWGs increased by 64% (IVM), 97% (MXD) and151% (IVM+RBZ) compared with the Control group. The effect of AR on live weightgains was significant (Tukey, P<0.05) in both forage resources. In conclusion,anthelmintic resistance has a high impact on beef cattle productivity.